ANALISIS APPRAISAL TEKS EDITORIAL PANGUDARASA DALAM MAJALAH PANJEBAR SEMANGAT - Wijayanti, Kenfitria Diah (PRASASTI: Journal of Linguistics, 2020)
This article explores Pangudarasa’s editorial texts in the Panjebar Semangat magazine by using a systemic theory of functional linguistics particularly an appraisal analysis of texts. The objectives of this research are (1) to identify the appraisal tools in Pangudarasa’s editorial texts in a Javanese magazine called Panjebar Semangat, and (2) to describe the perceptions of Pangudarasa’s editorial text writers in the Panjebar Semangat magazine. This descriptive qualitative research used a qualitative method along with a content analysis platform. The data pertaining to words, phrases, clauses, and sentences coincided with appraisal tools. The data source was derived from the Panjebar Semangat magazine, which was published on December 21, 2019 entitled Kasus Garuda, Wanci Kang Pas Kanggo Ngresiki BUMN. The data analysis used a method of referential matching tools to determine a phenomenon beyond the language. The results of data analysis show that (1) appraisal tools in the editorial texts of Pangudarasa in the Panjebar Semangat magazine dominantly present appreciation (42.55%), judgment (36.17%) and affect (21.28%), and (2) the pattern of writers' perceptions to support the Minister Erick Thohir's decision in handling the Garuda Airlines case. This support is reinforced by the use of language functions to influence others by assessing a case directly and authors of editorial texts have a tendency to tell sensitive things or issues mainly concerned with events in the community.